Current Status of Anaemia Among 6- 59-Month Old Children In India – What Does the NHFS Fact Sheet Speak? - Sahrawat, Neha; Sodhi, Avinash Kaur; Mishra, Sidharth Sekhar (Indian Journal of Community Health, 2022)
Introduction- India has the highest rate of child anemia among developing countries. To gain the most up-to-date picture of child anemia in India. We used the data of 6 to 59 months old children from the fifth cycle of the National Family Health Survey conducted in 2019–21. The study's goals were to shape the pervasiveness of anaemia in children in state of India, age group and zone, as well as the relationship between socioeconomic factors and anaemia. Methodology-The presented study is a secondary data analysis based on the data from the NFHS-5 and secondary literature. Results- The study found that in India in 2019– 21, 67.1% of children of specified age 6-59 months were anaemic, an increase of 8.5% points since the NFHS-4 study conducted in 2015–16 i.e., 67.1% and as compared with NFHS-4 (58.6%), despite of the significant increase in the consumption of iron-folic acid (IFA) tablets under INIPI. The data show that the number was higher in rural India (68.3 percent) compared to urban India (64.2 percent). Unfortunately, recent Economic development and the national anaemia control programme have not resulted in a significant reduction in anaemia prevalence in India. Conclusion- According to the study, the percentage of children in India was anemia increased by 8.5% in NFHS-5 as compared with previous NFHS-4 survey which found to be at 58.6%.